HUBUNGAN ANTARA DIKLAT DAN KOMPENSASI DENGAN PENINGKATAN KINERJA GURU PADA SEKOLAH DASAR NEGERI DI KOTA SOLOK - Arianto Tandika (al-fikrah: Jurnal Manajemen Pendidikan, 2019)
Many factors have correlation with teacher’s performance, likes training and compensation. The teacher is not optimal in following training proses and compensation for teacher is not maximum yet also has effects to teacher’s performance. The teacher as spearhead of education in learning process at school, so the teacher’s quality and standard of life should be improved and developed according to the present and the future life. The research has purpose to know the correlation training and compensation with teacher’s performance at state elementary school in Solok City. The research is quantitative research with correlational approach, in collecting data on research question. The technic collecting data is close questioner. The result is analyzed by use quantitative approach and use frequency table tools also statistic test by use SPSS program. Based on the result of data analysis there is a correlation between training and compensation with teacher’s performance has meaning to correlation has found 0.654 with references to the degree of relation belonging a strong correlation, therefore the hypothesis in this research is acceptable: